Seed Plant Endemism on Hainan Island: A Framework for Conservation Actions - Francisco-Ortega, Javier; Wang, Zhong-Sheng; Wang, Fa-Guo; Xing, Fu-Wu; Liu, Hong; Xu, Han; Xu, Wei-Xiang; Luo, Yi-Bo; Song, Xi-Qiang; Gale, Stephan (The Botanical review, 2010)
Hainan, the second largest island of China, has the most extensive and best preserved tropical forests of this country. A network of 68 protected areas (54 of them are terrestrial) provides in situ conservation for the unique ecosystems of the island. We: (1) discuss an updated check-list of seed-plant species that are endemic to Hainan, (2) evaluate the extent to which the endemic flora has been the subject of molecular studies, and (3) investigate the conservation status of these species. We recognize 397 endemic species on the island, 271 of which are reported in the protected areas, and 144 of which have been Red-Listed (85 assigned to the Critically Endangered (40) or Endangered (45) IUCN categories). The families with the highest number of endemics are Rubiaceae (33 species), Lauraceae (27 species), and Poaceae (26 species). The island has only seven endemic genera, all of which are unispecific. Compared with other tropical islands, Hainan has a low number of endemics but our preliminary observations suggest that the island has a highly disharmonic flora when compared with that from the mainland. Nevertheless, most of the major clades of the seed-plant tree of life with representatives in China also have endemic species on the island. We argue that the low levels of endemism reflect the continental nature of Hainan and the fact that several areas of the island have not been fully inventoried. We were unable to find a single molecular systematic study focusing exclusively on the Hainan endemics; however, 24 of the endemic species have been included in phylogenetic studies targeting particular genera or families. Future research/conservation actions for the endemic flora of Hainan should focus in developing: (1) a red-list that assesses all 397 endemic species, (2) comprehensive floristic studies for the protected areas, (3) molecular phylogenetic and conservation genetic studies with a primary focus on the endemics, (4) studies to understand what ecological interactions are important in the biology of the endemic species, and (5) eco-geographical studies to identify Important Biodiversity Zones of endemism within Hainan and therefore potential new protected areas.